2019
DOI: 10.35912/ijfam.v1i2.109
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of corporate social responsibility of property developers in Bauchi Metropolis, Nigeria

Abstract: The study aims to assess the corporate social responsibility of property developers in Bauchi metropolis with a view to examine the importance and effects of corporate social responsibility on property development in the study area. This study is limited to Bauchi metropolis. Research methodology: The study uses descriptive and exploratory research design using quantitative research approach. Questionnaires were administered to 20 property developers within Bauchi metropolis using purposive sampling techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…However, it has been shown that the influence persists in both wealthy and developing nations, as well as in and beyond the agricultural sector (Burke, Hsiang, & Miguel, 2015). In the Nigerian context, this was also confirmed by Tukur, Shehu, Mammadi, and Sulaiman (2019) citing relevant studies conducted in the Niger Delta region.…”
Section: Introductionmentioning
confidence: 85%
“…However, it has been shown that the influence persists in both wealthy and developing nations, as well as in and beyond the agricultural sector (Burke, Hsiang, & Miguel, 2015). In the Nigerian context, this was also confirmed by Tukur, Shehu, Mammadi, and Sulaiman (2019) citing relevant studies conducted in the Niger Delta region.…”
Section: Introductionmentioning
confidence: 85%
“…Ratul, Nayma, and Rahman (2023) in their research state that Corporate Social Responsibility (CSR) is vital since it affects the company, customers, and society. Public awareness of corporate social responsibility has grown in recent decades (Tukur, Shehu, Mammadi, & Sulaiman, 2019). CSR is the obligation of organizations to not only provide good goods and services to society, but also to maintain the quality of the social and physical environment and to contribute positively to the well-being of the communities in which they are located.…”
Section: Legitimacy Theorymentioning
confidence: 99%
“…Energy crises have impacted business dealings, the energy efficiency of a building is becoming increasingly important, sustainability is rising to the top of the corporate agenda, and security concerns have jumped to the top of the list. As a result, many businesses have begun reevaluating their definition of "core" activities in light of these new realities (Tukur, Shehu, Mammadi, & Sulaiman, 2019).…”
Section: Background Of the Studymentioning
confidence: 99%